Kepastian Hukum dan Perlindungan Investor PT. Jouska Finansial Indonesia dalam Hukum Pasar Modal Indonesia - Salsabila Aulia Shafti (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the legal position of PT. Jouska Finansial Indonesia in providing investment recommendations to investors under Law Number 8 of 1995 concerning the Capital Market, as well as to examine the implications of its unclear legal status on legal certainty and investor protection in Indonesian capital market practices. This research employs a normative legal research method using statutory and case approaches. The data sources consist of primary and secondary legal materials analyzed qualitatively. The results indicate that the activities conducted by PT. Jouska Finansial Indonesia juridically fulfill the elements of investment advisory services as regulated under Article 1 paragraph 11 of the Capital Market Law, due to the provision of specific and personalized investment recommendations to investors. However, such activities were carried out without authorization from the Financial Services Authority (Otoritas Jasa Keuangan/OJK), resulting in the absence of legal legitimacy within the Indonesian capital market legal framework. The unclear legal status consequently weakens legal certainty and investor protection, particularly concerning supervision, legal accountability, and dispute resolution mechanisms. Therefore, stronger regulations and supervision over financial education and consultation activities related to the capital market are necessary to ensure optimal legal certainty and investor protection.